2002
DOI: 10.1051/0004-6361:20020101
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric circulation and tides of “51 Pegasus b-like” planets

Abstract: Abstract.We examine the properties of the atmospheres of extrasolar giant planets at orbital distances smaller than 0.1 AU from their stars. We show that these "51 Peg b-like" planets are rapidly synchronized by tidal interactions, but that small departures from synchronous rotation can occur because of fluid-dynamical torques within these planets. Previous radiative-transfer and evolution models of such planets assume a homogeneous atmosphere. Nevertheless, we show using simple arguments that, at the photosph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

70
609
4
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 584 publications
(692 citation statements)
references
References 33 publications
70
609
4
1
Order By: Relevance
“…Observations of HD189733b (Knutson et al 2007(Knutson et al , 2009Agol et al 2010) appear to have convincingly demonstrated the existence of equatorial super-rotation, showing that the hottest point in the phase curve appears slightly before secondary eclipse, as first predicted by Showman & Guillot (2002). However, as we are able to characterize more planets, we are finding a wide variety of behaviors.…”
Section: Introductionsupporting
confidence: 68%
“…Observations of HD189733b (Knutson et al 2007(Knutson et al , 2009Agol et al 2010) appear to have convincingly demonstrated the existence of equatorial super-rotation, showing that the hottest point in the phase curve appears slightly before secondary eclipse, as first predicted by Showman & Guillot (2002). However, as we are able to characterize more planets, we are finding a wide variety of behaviors.…”
Section: Introductionsupporting
confidence: 68%
“…Several explanations have been proposed, and as more transiting planets have been discovered it is now clear that the size anomaly is closely related to the amount of incoming irradiation received from the host stars. Hot Jupiter atmospheres seem able to transfer a significant fraction of the incoming radiative energy into internal entropy, via one or several processes that may or may not include ohmic dissipation (Batygin and Stevenson, 2010), or eddy dissipation (Showman and Guillot, 2002;Youdin and Mitchell, 2010). Other explanations have been proposed for the anomalous radii but do not account for the observed dependence with stellar irradiation.…”
Section: Exoplanetsmentioning
confidence: 99%
“…Most theory papers focused on irradiated hot Jupiters, emphasizing spectral features and 1D temperature/pressure profiles resulting from the intense heating by the host star (Seager & Sasselov 1998;Marley et al 1999;Sudarsky, Burrows, & Pinto 2000;Barman, Hauschildt & Allard 2001. Cloud modeling (Ackerman & Marley 2001;Cooper et al 2003) and atmospheric 200 S. Seager circulation (Showman & Guillot 2002;Cho et al 2003) were also expected to be important. Calculation of exoplanet illumination phase curves, polarization curves (Seager, Whitney, & Sasselov 2000), and especially transmission spectra Brown 2001;Hubbard et al 2001) set the stage for observed spectroscopy during transit.…”
Section: Exoplanet Atmospheres: a Theoretical Outlookmentioning
confidence: 99%